Experimental Analysis of EN 19 Alloy Material on EDM for Improving Geometrical Errors Using Copper Pentagon Shaped Electrode. (2018) - Selvarajan, L.; Katherasan, D.; Srivijai, B.; Rajavel, R.; Ramamoorthi, M.
Abstract: In this research, an investigation and experimental work were carried out on electric discharge machining of EN19 alloy material using copper pentagon shaped electrode. Considering the input process parameters such as Current (amp), Pulse on time (µs) and pulse off time (µs), dielectric pressure (kg/cm 2 ) for machining the effect of this following input parameters on output characteristics like Material Removal Rate (MRR), Tool Wear Rate (TWR), Wear Ratio (WR) and machining time. The investigation was carried out using with L9 orthogonal array based on Design of Experiments (DOE). The effect of each machining parameters on output characteristics were studied independently using main effect plots using Minitab. The most significant factors affecting MRR and TWR of high speed EDM process have been identified as current, pulse on time, pulse off time in dielectric pressure.